(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
As it could not be otherwise, first of all, I wish to extend my gratitude to the Royal Academy of Medicine and Surgery of Valladolid for my appointment as Bankruptcy Academician -which for me is a true honor-, and especially to two of its Honorary Academicians, Dr. Mateo and Dr. Rabadán. Thank you, first of all, for your friendship and also obviously, for having proposed me for such a distinction. In short, I can say that my professional life is linked to assistance in the Public Health Service and Private Medicine in the specialty of General Surgery and Taurine Surgery.